(untitled) (Journal of Economic Research & Business Administration, 2016)
This article presents the results of research aimed at studying the inter national experience of depreciation policy and the possibility of applying international practices in the Republic of Kazakhstan. The study found that in countries with developed market economies, depreciation dominate the financing of investments and constitute the basis of the investment poten tial of the enterprises. Next comprehensively reviewed experience of the accelerated depre ciation of fixed assets in these countries. It was found that the use of accel erated depreciation of fixed assets allows in the short term to increase the technical capabilities of enterprises and rapidly raise the volume of their output. Accelerated depreciation methods, as an effective source of in vestment significantly exert pressure on the development of scientific and technical progress in the countries actively using them in their activities.